Dirty jokes and bawdy songs : the uncensored life of Gershon Legman - Davis, Susan G., 1953- (Folklore studies in a multicultural world., 2019)
"Collector of sexual folklore. Cataloger of erotica. Tireless social critic. Gershon Legman's singular, disreputable resume made him a counter-cultural touchstone during his forty-year exile in France. Despite his obscurity today, Legman's prescient work and passion for the prurient laid the groundwork for our contemporary study of the forbidden. Susan G. Davis follows the life and times of the figure driven to share what he found in civilization's secret libraries. Self-taught and fiercely unaffiliated, Legman collected the risque on street corners and in theaters and dug it out of little-known archives. If the sexual humor he uncovered often used laughter to disguise hostility and fear, he still believed it indispensable to the human experience. Davis reveals Legman in all his prickly, provocative complexity as an outrageous nonconformist thundering at a wrong-headed world while reveling in conflict, violating laws and boundaries with equal abandon, and pursuing love and improbable adventures. Through it all, he maintained a kaleidoscopic network of friends, fellow intellectuals, celebrity admirers, and like-minded obsessives"--